2008
DOI: 10.1590/s0034-70942008000100007
|View full text |Cite
|
Sign up to set email alerts
|

Bloqueio dos nervos ilioinguinal e iliohipogástrico guiado por ultra-sonografia associado à anestesia geral: relato de caso

Abstract: Ultrasound-guided iliohypogastric and ilioinguinal nerve block in patients undergoing outpatient inguinal herniorrhaphy can be done as an aid to postoperative analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Currently, most inguinal herniorrhaphies are performed as outpatient surgery. Thus, the use of anesthetic techniques that allow adequate postoperative analgesia as well as earlier recovery and hospital discharge is necessary 20 . Other studies also have demonstrated shorter duration of analgesia in II and IH nerve block.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most inguinal herniorrhaphies are performed as outpatient surgery. Thus, the use of anesthetic techniques that allow adequate postoperative analgesia as well as earlier recovery and hospital discharge is necessary 20 . Other studies also have demonstrated shorter duration of analgesia in II and IH nerve block.…”
Section: Discussionmentioning
confidence: 99%